Non-audit fees and auditor independence: Nigerian evidence. Issue 8 (26th June 2019) - Onulaka, Paul Nnamdi; Shubita, Moade Fawzi; Combs, Alan
Abstract : Purpose: This study aims to investigate the extent to which the provision of non-audit services (NAS) by external auditors to audit clients affects auditors' independence and the audit expectation gap in Nigeria. Design/methodology/approach: The study adopts an interpretivist approach. In total, 30 semi-structured, face-to-face interviews were conducted to explore the views expressed by audit partners and pension fund managers in Nigeria; group responses were evaluated and presented separately. After transcribing the interview audio recordings, a thematic data analysis of the two groups' responses was performed. Findings: Interpretation of the interview responses indicates that the provision of NAS by audit firms to their audit clients is regarded by auditors as a matter of economic necessity. Nevertheless, it is also perceived as impeding auditors' independence and increasing the gap between the auditor and public expectations. Practical implications: This study contributes to the debate surrounding the need for an independent body to oversee auditing standard setting distinct from the current practice to enhance transparency. Originality/value: A qualitative analysis of the nuanced responses obtained from the semi-structured interviews reveals starkly the perceived economic pressures on auditors to accept non-audit work. Moreover, it endorses the regulation to restrict non-audit work in support of a sustainable fee level for an independent audit.